Peran Orang Tua Dalam Mengembangkan Sikap Religiusitas Anak - Rahmatullah Akbar; Fajri Ismail; Muhammad Win Afgani (Jurnal Ilmiah Wahana Pendidikan, 2023)
The role is a set of behavior that is expected to be possessed by people who are domiciled in society, individual characteristics that are distinctive and special. Parents are the people who are primarily responsible for the education of children. Parents determine the future of children. The cultivation of religiosity values ​​(religiousness) according to Islam is implementing religious or Islamic teachings as a whole. Therefore, every Muslim both in thinking, behaving and acting is ordered to be Muslim. Parents have a role in growing the religiosity of their children. This is because children will grow and develop into adults, and will become part of society. The type of research used is qualitative research, literature study. This article discusses the meaning of the role of parents in developing a child's religious attitude, the role of parents, parents' obligations to children, the meaning of children’s religiosity, dimensions of child religiosity, and factors affecting children's religiosity